Evaluación del manejo de los desechos hospitalarios, Dirección Distrital 07D06 Santa Rosa– Salud en el primer semestre del año 2014. - Cabezas Aguilar, Cristian Xavier (2015)
Overall in hospital each year there are between 500 and 800 tons of medical waste the same as not having a proper and correct process of elimination can increase accidents on personal health this leads to many consequences as the presentation of infectious diseases such as HIV, Hepatitis B, C, which is 100% preventable why we decided to perform the following research had as general objective Determine the management of hospital waste in the District Direction 07D06 Santa Rosa-Health in the first half of the year 2014.